Negotiating Participatory Research Processes With Domestic Violence Program Staff to Obtain Ecologically Valid Data. Issue 23 (December 2019) - Nnawulezi, Nkiru; Sullivan, Cris M.; Marcus, Suzanne; Young, Latoya; Hacskaylo, Margaret
The choice of research design affects not only internal and external validity but ecological validity as well. Ecological validity refers to the extent to which data are based in and relevant to real-world settings. One way for researchers to maximize the likelihood of achieving ecological validity is to design studies with community partners that use participatory approaches. Engaging deeply with community partners in determining what to study, how to measure constructs of interest, interpreting results, and using findings to create change is one means of conducting research that is likely to produce findings that are meaningful to communities. Conducting in-depth, participatory research within agencies providing crisis supports to individuals who have experienced trauma creates an additional level of complexity in the research process. This article presents a case example of how academic researchers and staff members of a nonprofit organization working with survivors of intimate partner violence collaborated on an evaluation of the community partner agency. As part of this process, the team members had to be continually aware of and responsive to the nature of crisis-focused work. We provide a reflexive account of the lessons learned and recommendations for future research.